2015
DOI: 10.1021/acs.jpca.5b03912
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Properties Enthalpy, Entropy, and Heat Capacity of C1–C4 Fluorinated Hydrocarbons: Fluorocarbon Group Additivity

Abstract: Enthalpies of formation for 14 C2–C4 fluorinated hydrocarbons were calculated with nine popular ab initio and density functional theory methods: B3LYP, CBS-QB3, CBS-APNO, M06, M06-2X, ωB97X, G4, G4(MP2)-6X, and W1U via several series of isodesmic reactions. The recommended ideal gas phase ΔHf298° (kcal mol(–1)) values calculated in this study are the following: −65.4 for CH3CH2F; −70.2 for CH3CH2CH2F; −75.3 for CH3CHFCH3; −75.2 for CH3CH2CH2CH2F; −80.3 for CH3CHFCH2CH3; −108.1 for CH2F2; −120.9 for CH3CHF2; −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…In a previous study, we tested B3LYP, M06, M06‐2X, ωB97X, G4, CBS‐QB3, CBS‐APNO, W1U by using work reactions for fluorinated hydrocarbons and showed that the calculations were in close agreement and had good accuracy. The B3LYP method, which combines the three parameter Becke exchange functional, B3, with the Lee–Yang–Parr (LYP) correlation functional, has been widely used for stable molecules, transition states, and radicals.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we tested B3LYP, M06, M06‐2X, ωB97X, G4, CBS‐QB3, CBS‐APNO, W1U by using work reactions for fluorinated hydrocarbons and showed that the calculations were in close agreement and had good accuracy. The B3LYP method, which combines the three parameter Becke exchange functional, B3, with the Lee–Yang–Parr (LYP) correlation functional, has been widely used for stable molecules, transition states, and radicals.…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainty of a target molecule enthalpy depends on the uncertainty of work reaction calculation method, the uncertainty of reference species, and the number of isodesmic reactions . The calculation of uncertainty has been described in several previous studies . The calculated uncertainties listed in Table 2 are based on the CBS‐QB3 level calculation results of the targeted species, and the uncertainties of the reference species.…”
Section: Resultsmentioning
confidence: 99%
“…The Benson group additivity method has been widely used for the estimation of thermodynamic properties of hydrocarbons and oxygenated hydrocarbons due to its good relative accuracy and straightforward application . Results from the group additivity method for the species where groups were available in the literature are listed for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations